Willingness to be a partner in musharakah mutanaqisah home financing: empirical investigation of psychological factors = Kesediaan menjadi rakan dalam pembiayaan rumah musharakah mutanaqisah: kajian empirikal faktor-faktor psikologi - Amin, Hanudin; Abdul Rahman, Abdul Rahim; Abdul Razak, Dzuljastri (Universiti Kebangsaan Malaysia, 2014)
This study is aimed at explaining factors influencing the intention to be a partner amongst bank customers in musharakah mutanaqisah home financing. Drawing upon the theory of planned behavior (TPB), this study assesses the model in order to examine the effects of three explanatory factors namely attitude, subjective norm and perceived behavioral control on the intention to be a partner in the context of Islamic home financing. This study modifies the TPB to reflect musharakah mutanaqisah home financing. The model of the study is assessed using survey data from 168 respondents among bank customers. The findings suggest that attitude, subjective norm and perceived behavioral control are significantly influencing the intention to be a partner. The relationship between attitude and subjective norm is also significant. Thefindings demonstrate the applicability of the TPB in the musharakah mutanaqisah home financing context. The findings are also useful to bank managers in effectively managing Islamic home financing facilities.